POLLUTANTS EMISSION AND DISPERSION FROM FLARES:A GAUSSIAN CASE – STUDY IN IRAQ - Gzar, Hatam Asal; Kseer, Khamaal Muhsin (Al-Nahrain Journal of Science, 2018)
The aim of this research is to study the emission and dispersion of pollutants (HC, CO, NOx,SPM) from the elevated flares in three situations of South Gas Company for Liquefied Petroleum Gas (LPG) production in Al-Basrah Governorate in Iraq. These three situations are Khor Al-Zubair plant, North Al-Rumaila Plant, and Storage Complex. The number of flares in the situations are 5, 3, and 2 flares respectively. A mathematical model formulated in a computer program written in visual basic language was utilized in finding the ground level concentrations of pollutants HC, CO, NOx, and SPM emitted from the elevated flares of the three situations; the concentrations were found at selected sites inside and outside of each situation at different distances. The programmed model takes into consideration all the meteorological conditions (wind speed, wind direction, ambient temperature, and atmospheric stability) which may take place at the study region. The emission rates of the pollutants which are emitted from the elevated flares are found depending on the laboratory analysis of gas compositions send to the flares , also by utilizing the modern EPA methods for determination the emission rates. The results of research illustrate the meteorological cases which are more effect in causing the maximum ground level concentrations of pollutants especially the unstable atmospheric conditions and wind speed. On the other hand, the programmed model is utilized to find the concentrations of hydrocarbons (HC), propane (C3H8) , and butane (C4H10) which are released from flare column to the atmosphere in case of combustion failure of these gases, at areas adjacent to the situations of flares.